Manuskrip Al-Qur'an dari Sulawesi Barat Kajian Beberapa Aspek Kodikologi - Akbar, Alii (Lajnah Pentashihan Mushaf Al-Qur'an, 2014)
This article examines eight ancient Qur’ans of West Sulawesi. All of those manuscripts are from individual collections. The first part of this paper describes each of the manuscripts, and then discusses the text of the Qur'an as well as other additional texts, either at the beginning or at the end of manuscripts. The Qur’an which is studied in this article comes from the Bugis and becomes its tradition, although currently it is belonged to someone in Mandar, West Sulawesi. Rasm uthmani in the manuscript had been widely used in South Sulawesi, including Wajo and Bone, in the 19th century. The manuscript was also equipped with the reading of qira'at sab’ (seven styles of reciting the Qur’an) which is attached at the edge of the Qur’an. Of the eight Qur’ans reviewed in this paper, it was only one which has not a record of the qira'at note. Keywords: ancient Qur’an, West Sulawesi, illumination, Bugis.